Evaluación de la obtención y uso del aceite esencial de eucalipto (eucalyptus globulus) como fungicida (2020)
Fungi are one of the main causes of crop damage, which generates large economic losses. Currently, synthetic biocides are used, which are harmful to health and the environment. Different organic alternatives, such as essential oils, have been found that can mitigate these effects. Colombia has a large number of plants that have been little exploited and unexplored at the scientific level and that have demonstrated fungicidal properties; one of these is the common eucalyptus (eucalyptus globulus). In the present comprehensive degree work, the documentary review of different articles and case studies was carried out, both for the choice of the method of extraction of eucalyptus essential oil, and for its evaluation as a fungicide. Through this review, the vapor drags method was selected due to the amount of information found; and the different concentrations at which the eucalyptus essential oil inhibits the different fungi, as well as the factors that could affect this inhibition, were analyzed. Subsequently, and based on the case studies of the selected method, the optimal parameters for the process were determined and scaling up was done at the pilot level. The conditioning of the raw material referred to the selection, washing, drying and grinding of the leaves, and the operational parameters corresponded to the extraction time of 98 min, the condensation temperature at the inlet of 15 °C and at the outlet of 26.4 °C, the pressure of the equipment of 1 bar, the water vapor flow of 6,19 kg/h and the vapor temperature of 99.97°C. Consequently, the drying, grinding, extraction and temperature control equipment was specified. To complete the work, it was obtained that the process of obtaining the essential oil that responds to the established parameters could have a cost of $107.394 COP and together with the costs of purchasing equipment, it could have a total investment cost of $ 99’813.879 COP.